Petroleum subsidies in Yemen: Leveraging reform for development - Breisinger, Clemens; Engelke, Wilfried; Ecker, Olivier (International Food Policy Research Institute, 2011)
Petroleum subsidy reform is increasingly seen as an opportunity for consolidating public finances and fostering sustainable economic development. Yemen, as the country with the lowest per capita income in the group of countries with a high level of energy subsidies, started to reduce subsidies in 2010 and is discussing further options for reform. The results of this paper support a comprehensive petroleum subsidy reform in Yemen. Economic growth is projected to accelerate between 0.1 and 0.8 percentage points annually as a result of reform. Yet, the design of the reform is critically important, especially for the poor. Outcomes of alternative reform scenarios range from an increase in poverty of 2 to 6 percentage points. A promising strategy combines subsidy reduction with direct transfers of 13,800 to 19,700 Yemeni rials annually to the poorest 30 percent of households and enhanced public investments. Investments should focus on the utilities, transport, trade, and construction sectors to integrate economic spaces and create the platform for a restructuring of agricultural, industrial, and service value chains, which should encourage private sector led and job creating growth in the medium term.